Analisis Pelaksanaan Penilaian Autentik Mata Pelajaran Matematika dalam Pembelajaran Daring di Masa Pandemi Covid-19 di SDN Rajeg V - Kartini Kartini; Mawardi Mawardi; Samsul Azhar (RC-INSTITUT, 2021)
This research focuses on implementing authentic assessments of mathematics subjects in online learning. The purpose of this study was to describe the authentic assessment of mathematics subjects in online learning. This study uses descriptive qualitative methods with research subjects including fifth grade teachers. Data collection techniques in this study used observation,interviews and document studies. Technical analysis of the data using the data analysis component of Miles and Huberman's interactive model (data reduction,data presentation and conclusion drawing). Test the validity of the data using triangulation of sources, techniques and time. The main problem that will be discussed in this research is how to implement an authentic assessment of mathematics subjects in online learning. The results showed that the implementation of an authentic assessment of mathematics subjects in online learning during the Covid-19 pandemic at SDN Rajeg V was implemented well, this was seen when the teacher's assessment used the attitude, knowledge, and skills shutters and at the time of learning the teacher monitored the progress of students during the learning process. learning process, conducting written tests with assignments.